Study guides

☆☆

Q: How do you factor this x2 minus 13x plus 36?

Write your answer...

Submit

Still have questions?

Related questions

If that's plus 36, it factors to (x - 9)(x - 4) If it's minus 36, it gets ugly in a hurry.

x2 + 13x + 36 = (x + 9)(x + 4)

6(13x + 6)

(x + 4)(x + 9)

(x + 9)(x + 4)

(x + 9)(x + 4)

The factors of x2-13x+36 are 'x-9' and 'x-4'because the expression (x-9)(x-4) can be simplified as x2-13x+36.

(x-4)(x-9)

x2-13x+36 = (x-4)(x-9) when factored

x squared minus 12 x plus 36 = (x - 6)(x - 6)

x^2 - 13x + 36 = 0 Factor: (X-9)(X-4) = 0 X = 9 X = 4

x2 + 13x + 36 = 0 so (x+4)(x+9) = 0 so that x = -4 or x = -9

(x + 12)(x - 3)

(x - 9)(x - 4)

x2-13x+36=(x-9)(x-4)=0 x=9 or x=4

x sq equalls 36 and x equalls plus or minus 6

(6x - 1)(6x - 1)

(x+9)(x+4)

49x2 - 84x + 36 = (7x - 6)(7x - 6) or (7x - 6)2

36 + 42 - 6 + 28 - 43 + 81 - 6 = 132

Well, if that was a - 13X we could factor by inspection, but now the quadratic formula is needed. By inspection the discriminant yields two real roots. X^2 + 13X + 36 = 0 X = - b (+/-) sqrt(b^2-4ac)/2a a = 1 b = 13 c = 36 X = - 13 (+/-) sqrt[b^2 - 4(1)(36)]/2(1) X = - 13 (+/-) sqrt(169 - 144)/2 X = - 13 (+/-) sqrt(25)/2 X = [- 13 (+/-) 5]/2 X = - 4 ------------ X = - 9 -----------

9x2 + 27x - 36 = 9(x2 + 3x - 4) = 9(x + 4)(x - 1)

x-4 is the correct answer for Apex

x2-5x-36 = (x-9)(x+4) when factored

It is: -234-36+32 = -238